Association of Aortic Valve Calcification to the Presence, Extent, and Composition of Coronary Artery Plaque Burden: ROMICAT Study - Mahabadi, Amir A. (2009)
BACKGROUND: Aortic valve calcification (AVC) is associated with cardiovascular risk factors and coronary artery calcification. We sought to determine whether AVC is associated with the presence and extent of overall plaque burden, as well as to plaque composition (calcified, mixed, and non-calcified). METHODS: We examined 357 subjects (mean age: 53 ± 12 years, 61% male) who underwent contrast-enhanced ECG-gated 64-slice multi-detector computed tomography from the ROMICAT trial for the assessment of presence and extent of coronary plaque burden according to the 17-coronary segment model and presence of AVC. RESULTS: Patients with AVC (n=37, 10%) were more likely than those without AVC (n=320, 90%) to have coexisting presence of any coronary plaque (89% vs. 46%, p<0.001) and had a greater extent of coronary plaque burden (6.4 segments vs. 1.8 segments, p<0.001). Those with AVC had over 3-fold increase odds of having any plaque (adjusted odds ratio [OR] 3.6, p=0.047) and an increase of 2.5 segments of plaque (p<0.001) as compared to those without AVC. When stratified by plaque composition, AVC was associated most with calcified plaque (OR 5.2, p=0.004), then mixed plaque (OR 3.2, p=0.02), but not with non-calcified plaque (p=0.96). CONCLUSION: AVC is associated with the presence and greater extent of coronary artery plaque burden and may be part of the later stages of the atherosclerosis process, as its relation is strongest with calcified plaque, less with mixed plaque, and nonsignificant with non-calcified plaque. If AVC is present, consideration for aggressive medical therapy may be warranted.